INFLUENCE OF DIFFERENT PLANT-BASED OILS AND FATS ON MURINE BIOCHEMICAL PROFILES - Salah, Al-Obaidi (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Fatty acids, carboxylic acids with hydrocarbon chains spanning between 4 and 36 carbons, play pivotal roles in various biological processes. This article explores the significance of fatty acids in cellular metabolism, particularly focusing on their synthesis, regulation, and impact on lipid and cholesterol metabolism. Fatty acid metabolism is intricately linked to an organism’s nutritional status, with lipogenesis being highly active in well-fed individuals with a carbohydrate-rich diet, and suppressed during caloric restriction or in conditions like diabetes mellitus. Cholesterol, a vital component of animal tissues, exists in various forms, including as lipoproteins and esters. Cholesterol esters serve as common storage and transit forms, while free cholesterol can be converted into bile acids. Unsaturated fatty acids in cell membranes’ phospholipids are crucial for maintaining membrane fluidity, highlighting their significance in cellular function. High-Density Lipoproteins (HDL) and Low-Density Lipoproteins (LDL) play key roles in transporting cholesterol to and from the liver. HDL, often referred to as "good cholesterol," is involved in cholesterol exchange and disposal in the bile. Additionally, this article touches upon clinical disorders related to fatty acid metabolism, with a focus on oxidation mechanisms. Triacyl glycerides, composed of fatty acids and glycerol, represent the most abundant lipid family in animals and plants and serve as essential storage lipids.